(untitled) - Jespersen, Otto (London, 1988)
London 1924 1st Allen & Unwin. 8vo., 859pp., index, hardcover. Near Good, inner hinges cracked, lower corners bumped, spine ends a bit frayed.
Keywords: Language and languages,Ngôn ngữ và ngôn ngữ; Philosophy,Triết học